(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes how phonetic, grammatical and lexical difficulties arise in teaching the Russian language and how to find ways to prevent them. In addition, examples given on certain topics are studied. Attention is drawn to the study of tenses and types of the verb. Learning these verbs helps students to freely use the richness of the Russian language.